Drivers of species richness and compositional change in Scottish coastal vegetation. Issue 2 (24th November 2016) - Pakeman, Robin J.; Hewison, Richard L.; Lewis, Rob J.
Abstract: Question: What are the main drivers of vegetation change within coastal dune and machair habitats and are these amenable to action to protect biodiversity at a local and national scale? Location: Coastal areas of Scotland. Methods: A national‐scale, quadrat‐based re‐visitation survey was used to assess where changes were occurring in terms of species richness and composition. Regression trees and linear mixed modelling were used to identify the main drivers of change between 1976 and 2010. Results: There were losses of habitat to erosion (4.7% of previously visited quadrats) and development (2.3%). Species richness changes were largely positive where sand dune and machair habitats remain part of an agricultural management system in the Inner and southern part of the Outer Hebrides. Richness losses were driven by acidic deposition and reduced grazing. Compositional changes were less related to agricultural changes, climate change and pollutant deposition than species richness changes. Conclusions: Reintroduction of grazing to coastal areas appears to be a policy that would have positive effects on biodiversity, as would continued efforts to reduce atmospheric deposition and coastal planning that allowed for realignment as sediment supply decreases and sea level rise continues. Abstract : A quadrat‐based revisitation survey was used to identify drivers of species losses and gains in Scottish sand dunes. Richness losses in eastern Scotland were driven by acidic deposition and reduced grazing. Species richness changes were neutral/positive where sand dune and machair habitats remained part of agricultural systems on the Hebridean islands.